Structural Behavior of Lightweight Composite Slab System - Sutiman, Nur Adidah; A. Majid, Masni; Jaini, Z. M.; Roslan, Aina Syafawati (International Journal of Integrated Engineering, 2021)
This study investigate the structural behavior of lightweight composite slab system that consist of profiled steel sheet (PSS) attached to dry board (DB) using mechanical screws and with or without infill materials. A total four full-scale panel specimen were tested under four-point bending when subjected under static loading. Result of the four-point test shows that increasing the thickness of profiles steel sheet gives major effect to the deflection and ultimate load. The deflection and ultimate load of 1.0mm thick panel specimen is 16.45% and 34.45% respectively. Therefore, increased the thickness of profiled steel sheet can enhance the stiffness and strength of the lightweight composite slab systems. It also found that the infill material used in these experimental gives minor effect to deflection and ultimate load. The deflection and ultimate load of panel specimen with foamed concrete is 21.18% and 16.66% respectively.  Thus, foamed concrete can be used only for non-structural purposed only such as sound proofing and fire resistance.